New species and host plants of Hexachaeta Loew (Diptera: Tephritidae) from Colombia - Clavijo, Pedro Alexander Rodriguez (Zootaxa, 2025)
Hexachaeta cundiboyacensis Rodriguez, a new species of the colombiana species group is described and illustrated. In addition, the first biological information on host plants and natural enemies for the colombiana species group is provided. Host plants include: Aegiphila alba Moldenke (Lamiaceae) for H. colombiana Lima and Aegiphila integrifolia (Jacq.) B.D. Jacks. (Lamiaceae) for the new species described here. The wasp Opius (Bellopius) hexachaeta Kula and Aguirre (Braconidae) was found parasitizing the new species. A modification of the species key of Hernández-Ortiz (1999) to incorporate this new species is also presented.